Analisis Tingkat Kepuasan Belajar Siswa Terhadap Fasilitas Ruangan Kelas di SMP Swasta Idanoi - Lase, Florida; Buulolo, Osisio; Ggulo, Testing Ilmiah; Harefa, Noveri Amal Jaya (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to describe the level of student satisfaction with the facilities in Idanoi Private Junior High School. This research uses a qualitative method, a descriptive approach. In the research, the researcher used variables, namely student satisfaction and learning facilities so that information about it was obtained, then conclusions were drawn. The data collection techniques used are observation, interviews, observations, dissemination of questionnaires, and documentation. Data collection with data analysis, data collection is an integral part of data analysis activities. Data analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusion drawing. The results of the data analysis show that the level of student satisfaction at Idanoi Private Junior High School is already satisfied, where the school has equipped all classroom facilities, Idanoi Private Junior High School in the classroom is included in the high criteria because the classroom is very adequate, free and has near-perfect completeness so that it can be used as a comfortable, neat and effective learning place